(untitled) (Web of Teachers: Inderscience Research, 2025)
This article analyzes the factors influencing speech development in children with disabilities and the necessary conditions for their effective speech formation. It highlights the importance of the psychological, pedagogical, and social environment in the development process. The article emphasizes the role of special educational institutions, art therapy methods, individualized approaches, and family support in enhancing speech development.